The year that changed our world - Eudes, Marielle; Taylor, Ruth (Translator); Aubenas, Florence; Melandri, Francesca; Agence France-presse (London New York, New York Thames & Hudson, 2021)
The Year That Changed Our World is the definitive, visual history of the Covid-19 Pandemic. With more than 400 photographs, this ambitious publication traces the arc of the Pandemic from China in early 2020 through to the vaccine breakthroughs of Spring 2021. Behind the relentless nature of the daily news since the events on Wuhan in early 2020 first broke, and the sense of fear and trepidation that the rapidly developing events provoked, what have we seen of the real stories of the world during the Pandemic? What can be told of how we lived through the pandemic and of the resilience, resourcefulness and sense of purpose with which we coped and adapted to the challenges we faced? How can we make sense of what we went through? The photographers of Agence France Presse are uniquely placed to be able to document the deeper, human stories of the Pandemic. Active in more than 150 countries, they have been able to capture all angles of the Covid-19 story. Organized into six chronological parts interleaved with thematic sections, including sport, animals and leisure, The Year That Changed Our World presents a comprehensive view, showing the extraordinary efforts to understand, control and cope with a previously unknown virus alongside the human stories of our lives at home: playing, caring, watching and sharing, both together and at a distance. Edited by Marielle Eudes, Director of Photography at Agence France Presse, and with an introduction by Eudes and further texts, quotes and insights from a range of contributors and public figures, The Year That Changed Our World is the definitive visual document of humankind's resilience in the face of the pandemic and the perfect way of understanding and showing to future generations the world during the time of Covid-19.
Introduction: a true tale of dystopia / Marielle Eudes -- Winter 2020 -- The virus arrives in France: muddling through as best we can / Florence Aubenas -- Spring 2020 -- A letter from Italy: this is what we know about your future / Francesca Melandri -- Summer 2020 -- Autumn 2020 -- Winter 2021 -- Spring 2021.
Subtitle on cover: A photographic history of the COVID-19 pandemic.
Originally published as Pandemia by Agence France Presse, 2021.
In English, translated from the French.
111165
Keywords: COVID-19 Pandemic, 2020- -- Pictorial works; Covid-19 Pandemic, 2020- -- Social aspects -- Pictorial works; Documentary photography; art photography; Photography, Artistic; photobooks